G224(P) Glasgow Coma Scale or AVPU what do clinicians use in head injury? Does it matter?. (27th April 2016) - Nuttall, A; Patton, K; Kemp, AM
Abstract : Aims: To evaluate the use and equivalence of Glasgow Coma Scale (GCS) and AVPU in children with head injury. Methods: Ascertainment: children <15 years, admitted to 90% of UK hospital with head injury (September 2009–February 2010). Data recorded included GCS+/AVPU at the scene of injury and in the emergency department, age, hospital type, CT head scan. Outcome measures: scale used to assess level of consciousness, the equivalence of AVPU to GCS, GCS at the scene prediction of GCS in ED, CT scan result. Results: 91% (5168/5700) of children had their level of consciousness recorded in the ED (43%GCS, 30.5%GCS+AVPU, 17.3%AVPU), 66.1%(1190) of 1801 transported to hospital by ambulance had their level of consciousness recorded at the scene (33%GCS, 26%GCS+AVPU, 7%AVPU). The proportion of children who had no recording or AVPU only was greatest for infants, the use of GCS only increased with age (see Figure 1 ). GCS recorded at the scene predicted the same GCS in the ED in 77.4% (705/911) of cases. GCS=15 at the scene had specificity of 72.2% and sensitivity of 87.9% for predicting GCS=15 in the ED. 11.3% (73) of children with a GCS=15 at the scene had deteriorated when in ED. Correlation between AVPU scores and median GCS in 1147 children <5 years was A=GCS of 15, V=14, P = 8, U=3 and for 1163 children >5 years: A=15, V=13, P = 11, U=3. The proportion of children who had abnormality identified on CT was 3.7%(95% CI:3–4.5)(91/2443) for children GCS=15 and 4.3%(95% CI:3.1–5.7)(40/940) if AVPU=A and 15.9(95% CI13.2–19.2)91/570 if GCS <15, 19.6(95% CI:10.6–33.2)9/46 when AVPU= V, P or U. Conclusion: Despite NICE head injury guidelines, 26% of children in ED and 40% at the scene failed to have GCS recorded. AVPU was the most frequent method used for infants. GCS at the scene showed good prediction of GCS in ED, however one in ten children with GCS=15 at the scene deteriorated prior to hospital admission. This study is the first to give equivalence of AVPU to GCS in children which varied slightly between children <5 years and those > 5 years. However the method used did not influence the clinical outcome in terms of CT result.